Wirausaha Inovasi Produk Puding Ubi Unggu Dengan Penambahan Vla Gula Merah - Yuti Anita; Vineza Elsafa; Naufal Aziz Alfikri; Jejen Pratama Saputra; Wahyu Sucipto; Eko Sumartono (Pakis Journal Institute, 2024)
The entrepreneurial activity of product ivonation